When the fever will not stop, stop the pills!: a case report - Matos, César Ricardo Coimbra de; Beirão, Eduarda Maria da Conceição Sério Pereira; Neves, Rafael Simões; Assunção, António José; Marques, Rui Moreira (São Paulo Medical Journal, 2025)
Neuroleptic malignant syndrome (NMS) is a neurologic emergency potentially fatal. This rare side effect is most commonly associated with first-generation antipsychotics and less frequently with atypical or second-generation antipsychotics. The diagnosis relies on both clinical and laboratory criteria, with other organic and psychiatric conditions being ruled out. CASE REPORT: A 39-year-old female patient, who is institutionalized and completely dependent, has a medical history of recurrent urinary infections and colonization by carbapenem-resistant Klebsiella pneumoniae. Her regular medication regimen included sertraline, valproic acid, quetiapine, risperidone, lorazepam, diazepam, haloperidol, baclofen, and fentanyl. The patient began experiencing dyspnea. Upon physical examination, she exhibited hypotension and a diminished vesicular murmur at the right base during pulmonary auscultation. Initially, after hospitalization, she developed high febrile peaks associated with hemodynamic instability, prompting the initiation of antibiotic treatment. Despite this, her fever persisted without an increase in blood inflammatory parameters, and she developed purulent sputum, necessitating antibiotherapy escalation. The seventh day of hospitalization showed no improvement in symptoms, suggesting NNMS as a differential diagnosis. All antipsychotic and sedative drugs, as well as antibiotherapy, were discontinued, after which the patient showed significant clinical improvement. CONCLUSION: Antipsychotic agents are commonly employed to manage behavioral changes linked to various disorders. However, their severe side effects necessitate a high degree of vigilance, the cessation of all medications, and the implementation of supportive care measures. A prompt and accurate diagnosis of NMS is crucial to alleviating the severe, prolonged morbidity and potential mortality associated with this syndrome.